The impact of sports business resilience, innovative broadcasting strategies, and co-creation strategy on consumption of sporting events with the moderating role of team performance: A case study on San Miguel Corporation - Lin, Gjonn Tedmoore L. (Animo Repository, 2022)
The aim of this study is to examine, explain, and describe the impact of Sports Business Resilience (SBR), Innovative Broadcasting Strategies (IBS), and Co-Creation Strategies (CCS) on Sports Consumption (SC) with the added moderating effect of Team Performance (TP) to identify the best possible courses of action to recover from the repercussions of the COVID-19 pandemic to the sports industry. To achieve this, the researchers conducted an interview on a key person in the management of the organization. Results of the study show that SBR affects the occurrence of consumption, IBS impacts accessibility and intention for consumption, and CCS influences fans’ inclination to rewatch and support future games. However, unique from the other variables, only consumption from IBS is disturbed by presence of TP. Thus, the researchers concluded that the proper course of action for SBR is the maximization of trend changes in the aspect of the 4Ps. For IBS, utilizing existing innovative technologies in enhancing the factors of content, perceived usefulness, and ease of use, and minimizing effects of TP. Lastly, for CCS, capitalizing the hedonic engagement and humanitarian interest of consumers.